Detection of Theileria parva in the salivary glands of Rhipicephalus appendiculatus: Evaluation of staining methods - Voigt, Wolf P.; Mwaura, S.N.; Njihia, G.M.; Nyaga, S.G.; Young, A.S. (Springer, 1995)
A comparison of ten methods for staining tick salivary glands for detection of Theileria parva infection from ticks fed on rabbits for various periods was under taken. Staining with azure without hydrochloric acid hydrolysis was found to be the most reliable method for detection of the presporozoite stage (sporoblasts) of T.parva in the salivary gland acini of unfed Rhipicephalus appendiculatus and could be applied to field ticks. All the stains proved suitable for the detection and quantitation of sporozoites in ticks fed for 4 days on rabbits. The capacity of the stains to allow detection of early stages of T. parva differed, but it became more reliable during tick feeding as sporoblasts developed and matured. Giemsa's stain and Feulgen's stain followed by superimposition of Giemsa's stain were superior to other stains for the detection and quantitation of immature salivary gland stages in feeding ticks.